Thermal conductivity measurements for organic liquids at high pressure. (January 2020) - Yebra, Francisco; Troncoso, Jacobo; Romaní, Luis
Highlights: A new apparatus for thermal conductivity determination is presented. It works in the (288.15–313.15) K, (0.1–60) MPa temperature and pressure ranges. A metrological analysis is carried out yielding an uncertainty about 4%. Comparison with available literature data confirms the methodology reliability. New data are reported for compounds with assorted chemical nature. Abstract: A new instrument for determining the thermal conductivity as a function of temperature and pressure for liquids is described. The system is based on the transient hot wire technique. It is totally automatized: pressure and temperature are controlled and voltage drop through the wire is acquired using a digital system, which automatically performs all required actions. The instrument calibration can be made using only one reference liquid over the whole temperature and pressure ranges. Using rigorous metrological methodologies, it was found uncertainty in thermal conductivity to be around 4%. The thermal conductivity for methanol, ethanol, 1-propanol, heptane, octane, toluene, 1, 3-dichloropropane, 1, 2-dichloropropane, 1-nitropropane, propionitrile, propionic acid and 1-propylamine, was determined in the temperature and pressure ranges (283.15–313.15) K and (0.1–65) MPa. These data are compared with available literature values; good agreement was obtained for all liquids, which reveals the validity of the experimental procedure. Thermal conductivity data as well as their dependency against temperature and pressure are discussed in terms of the chemical nature of the studied compounds.